2005
DOI: 10.1007/s00109-005-0639-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor-related receptors, a subfamily of orphan nuclear receptors, as new tumor biomarkers in ovarian cancer cells

Abstract: A subfamily of orphan receptors, estrogen receptor-related receptors (ERRs), has been demonstrated to modulate the transcription of some estrogen responsive genes via variant estrogen response elements (EREs). This study was conducted to determine whether human ERRalpha, ERRbeta, and ERRgamma might be involved in the tumorigenesis of ovarian cancer. RT-PCR was performed to analyze the expression of hERRalpha, hERRbeta, hERRbeta-2, and hERRgamma mRNA in five ovarian cancer cell lines as well as 33 samples of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
119
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 32 publications
10
119
1
Order By: Relevance
“…The association of ERR␣ expression in breast cancer with a poor clinical outcome suggests it plays a role in tumor progression and aggressiveness (43,44,46). Evidence of similar correlates that appear in cancers of the prostate (79), ovary (80), colon (81), and endometrium (82) continue to emerge. Because its function is generally constitutive, ERR␣ could potentially induce ER␣ target genes in hormonally responsive cancers in an estrogen-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The association of ERR␣ expression in breast cancer with a poor clinical outcome suggests it plays a role in tumor progression and aggressiveness (43,44,46). Evidence of similar correlates that appear in cancers of the prostate (79), ovary (80), colon (81), and endometrium (82) continue to emerge. Because its function is generally constitutive, ERR␣ could potentially induce ER␣ target genes in hormonally responsive cancers in an estrogen-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 It has been suggested that there is a key role of ERRs in the regulation of the estrogen signal pathway in tumors, though the mechanisms of this crosstalk are still unclear. 34,35 Ariazi et al 36 observed that an increased ERRg level was associated with preferred clinical outcomes; ERRg was overexpressed in 75% of breast cancer. A similar result found in ovarian cancer by Sun et al 35 suggested that ERRg seems to be a tumor marker for a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the receptor is essential for the regulation of mitochondrial biogenesis exerted by PGC-1␣ (23,24). ERR␣ is also expressed in a wide variety of tissues, and its high expression correlates with poor prognosis in breast, colon, and ovarian cancers (25)(26)(27)(28)(29). This suggests a role for ERR␣ in cell proliferation and/or invasion, which remains to be determined.…”
mentioning
confidence: 99%